2021
DOI: 10.1186/s12872-021-01861-6
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between lipoprotein(a) and coronary atherosclerotic lesion is stronger than LDL-C, when LDL-C is less than 104 mg/dL

Abstract: Background Lp(a) and LDL-C are both risk factors of atherosclerotic cardiovascular disease (ASCVD). But there was a contradiction point in LDL-C and Lp(a) control. The appropriate level of LDL-C and Lp(a) in the prevention of ASCVD is still pending. Objective To investigate the correlation of Lp(a) and coronary atherosclerotic lesion, and find out the balance point in LDL-C and Lp(a) control. Method 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In patients treated with high-efficacy statins who achieved very low LDL-C levels in the primary prevention setting, Lp(a) levels were found to be a determinant of residual ASCVD risk 8. A correlation between Lp(a) levels and coronary heart disease (CHD) has been found in patients with low LDL-C (<104 mg/dL) 9. Overall, available evidence shows that Lp(a) is an ASCVD risk factor independent of LDL-C levels 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…In patients treated with high-efficacy statins who achieved very low LDL-C levels in the primary prevention setting, Lp(a) levels were found to be a determinant of residual ASCVD risk 8. A correlation between Lp(a) levels and coronary heart disease (CHD) has been found in patients with low LDL-C (<104 mg/dL) 9. Overall, available evidence shows that Lp(a) is an ASCVD risk factor independent of LDL-C levels 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…LDL binds to free cholesterol in the blood and can be oxidized to oxidized LDL (ox-LDL), which can promote macrophages to become foam cells, leading to the formation of atherosclerosis. 20 In the current study, after adjusting for other clinical indexes, LDL was identified to be an independent factor for the degree of CAS.…”
Section: Discussionmentioning
confidence: 56%
“…However, a single‐center cross‐sectional study was recently conducted to investigate the association between Lp(a) and coronary atherosclerotic lesion using Gensini score, Li et al found the association was influenced by LDL‐C levels. They revealed that Lp(a) was the risk factors of coronary atherosclerotic heart disease in patients with LDL‐C<100 mg/dl 27 . Therefore, the evaluation of Lp(a) in patients with well controlled cholesterol remained to be further studied.…”
Section: Discussionmentioning
confidence: 99%